1989
DOI: 10.1159/000181102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fenfluramine and Ritanserin on Prolactin Response to Insulin-Induced Hypoglycemia in Obese Patients: Evidence for Failure of the Serotoninergic System

Abstract: In order to study the hypothesized impairment of the serotoninergic system in human obesity, an insulin tolerance test (ITT) was carried out on 12 obese normoprolactinemic women and on 6 normal-weight women before (A) and after (B) the administration of a serotoninergic drug, fenfluramine (60 mg twice a day per os for 7 days). After a washout period, a new ITT (C) followed the administration of fenfluramine at the same dose, associated with a specific S2 blocker receptor agent, ritanserin (30 mg/day for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Furthermore, the present results agree with those obtained in human studies showing a normalization of GH response to arginine by FF in obese patients (Altomonte et al, 1987). Finally, they confirm our previous report (Bernini et al, 1989) in which this drug was found to restore PRL responsiveness to IIH in these patients.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the present results agree with those obtained in human studies showing a normalization of GH response to arginine by FF in obese patients (Altomonte et al, 1987). Finally, they confirm our previous report (Bernini et al, 1989) in which this drug was found to restore PRL responsiveness to IIH in these patients.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, healthy obese subjects have decreased prolactin responses to insulin‐induced hypoglycaemia and TRH stimulation (Donders et al ., 1985; Weaver et al ., 1990). Impairment of the serotoninergic (Bernini et al ., 1989; Pijl et al ., 1993) and the opioidergic (Argenio et al ., 1991) pathways have been implicated in this impaired modulation of prolactin release.…”
Section: Discussionmentioning
confidence: 99%